The Role of Reading Skills in Understanding Classical Arabic Texts: Challenges and Solutions for Students - Danil Mesa; Aldi Muhammad Alfin; Quratun Aini (Journal of Arabic Literature, Teaching and Learning, 2025)
This study aims to analyze the problems faced by students in mastering Arabic reading skills and to find appropriate solutions to improve their abilities. Reading skills are considered the main gateway to understanding Arabic texts, both in the context of other language skills (listening, speaking, writing) and in understanding Islamic teachings such as the Quran, hadith, and classical books. The research method used is qualitative research with a case study approach to students' difficulties in reading Arabic texts, including limited vocabulary, difficulty in understanding sentence structure, and weak phonological mastery. The results show that the reading learning process takes place in stages, starting from mastery of letters and sounds (phonetics), vocabulary enrichment, to understanding nominal and verbal sentence structures. These findings confirm that phonological mastery is the main foundation, while vocabulary enrichment and understanding of grammar are determining factors for reading success. The implication of this research is the need for a systematic and continuous reading teaching strategy, with an emphasis on phonological exercises, vocabulary development, and understanding of language structure so that students are able to understand classical Arabic texts more optimally.